(untitled) (Baghdad Science Journal, 2025)
In the present work we prepared heterojunction not homogenous CdS/:In/Cu2S) by spray and displacement methods on glass substrate , CdS:In films prepared by different impurities constration. Cu2S prepared by chemical displacement method to improve the junction properties , structural and optical properties of the deposited films was achieved . The study shows that the film polycrystalline by XRD result for all film and the energy gap was direct to 2.38 eV with no effect on this value by impurities at this constration .